Someone like you eaudiobook - Kingsbury, Karen (Baxter Family Collection., 2020)
Now a major motion picture starring Sarah Fisher! Science raises questions only hope and faith can answer in this instant New York Times bestselling "tale of forgiveness and love" ( Woman's World ) from Karen Kingsbury. Andi Allen is shaken to the core when she finds out everything she believed about her life was a lie. Her parents had always planned to tell her the truth about her past: that she was adopted as an embryo. But somehow the right moment never happened. Then a total stranger confronts Andi with the truth and tells her something else that rocks her world—Andi had a sister she never knew about. Betrayed, angry, and confused, Andi leaves her new job and fiancé, rejects her family's requests for forgiveness, and moves to Birmingham to find out who she really is. Dawson Gage's life was destroyed when London Quinn, the only girl he ever loved, is killed. In the hospital waiting room, London's mother reveals that London might have had a sibling. When Dawson finds Andi and brings her to Birmingham, the Quinns—her biological parents—welcome her into their lives and hearts. Andi is comforted by the Quinns' love and intrigued by their memories of London, who was so much like her. Is this the family and the life she was really meant to have? Now it will take the love of Dawson Gage to help Andi know who she is...and to help her find her way home in this "emotional, thoughtful tale" ( Publishers Weekly ). Some of the original characters names and locations in this edition of Someone Like You have been changed to correspond with the film adaptation of the book.